Digital communication model in increasing public trust : (Case study of Bawaslu Magelang Regency in the 2024 presidential election) - Kusuma, Alan; Dwihantoro, Prihatin; Ilham Nova Rizal, Muhammad (Universitas Ahmad Dahlan, 2024)
This study aims to develop a digital communication model to enhance public trust in election monitoring in Magelang Regency, classified as a high-risk area in the 2024 elections. Using a qualitative method with a case study approach, involving observation, interviews, and documentation, the research focuses on creating a communication model that effectively increases public trust. The findings reveal that digital communication implemented by Bawaslu through social media is more effective in engaging the public, but synchronization with the website requires improvement to ensure better information transparency. Website management is centrally integrated to facilitate maintenance and address server issues, with hosting responsibilities handled at the national level, while local branches are limited to content management without access to modify the website. This study recommends a digital communication model that provides practical guidelines for creating digital content to strengthen public trust in election monitoring institutions.